Sovereign debt at the crossroads challenges and proposals for resolving the third world debt crisis - Jochnick, Chris; Preston, Fraser A.; Oxford eBooks (Oxford : Oxford University Press, 2006)
This is a comprehensive overview of the problems associated with Third World debt and describes new and practical approaches to overcoming them. As contributions come from leading thinkers across a range of disciplines, the text offers a timely guide for understanding and influencing the debt debate.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Debts, External -- Developing countries; Debt relief -- Developing countries; Electronic books